Nomadic beekeeper movements create the potential for widespread disease in the honeybee industry. Issue 8 (17th June 2014) - Gordon, R; Bresolin‐Schott, N; East, IJ
<x xml:space="preserve">Abstract</x> Objective To examine the nomadic movements of Australian beekeepers and determine their potential to assist the spread of pests and diseases. Methods A questionnaire was mailed to all beekeepers in Australia who maintained >100 hives, requesting information on the location of their home base, locations used throughout the year and the crops that the bees fed on in each location. The information was analysed using network analysis software and a geographic information system. Results Nomadic Australian beekeepers formed a connected network linking 288 locations from central Queensland to western Victoria. A second, smaller network included 42 locations in south‐eastern South Australia. Almond orchards in Robinvale and Boundary Bend and lucerne seed production in Keith were locations of major hive congregations driven by the opportunity to provide paid pollination services. In the 3 months after completion of almond pollination in August 2008, movement of hives occurred from Robinvale and Boundary Bend to 49 locations, ranging from south‐east Queensland to south‐west Victoria. Discussion The movements identified in this study highlight the potential for rapid spread of disease or pests throughout the beekeeping industry should an incursion occur.